Studi Faktor Pendorong dan Risiko Penghambat Keputusan Investasi di Generasi Z: Studi Kasus Mahasiswa (Jurnal Ekonomi Bisnis dan Akuntansi, 2024)
Investment is a crucial part of economic activity, and Generation Z students should be at the forefront of participating. This article examines the extent to which students have engaged in investment activities by examining gender factors and exploring various factors driving investment interest, as well as inhibiting factors such as concerns and risks. This qualitative study, with 62 final-year students as respondents, involved a chi-square test. Data processing techniques used included a chi-square test to examine the influence of gender, and a thematic analysis to categorize the factors driving and inhibiting investment based on emerging themes. The findings indicated that 37 students intended to invest, while the remaining 25 stated they were not investing. The chi-square test indicated no significant gender influence on investment activity. Factors driving investment were the desire to think strategically in the face of an uncertain future and parental encouragement. Meanwhile, students who had not yet invested stated that a lack of capital due to a lack of income was another obstacle, as well as a risk. Other obstacles included limited knowledge and difficulty filtering information, as well as psychological and planning factors such as a lack of courage to face risks and concerns about fraudulent investments. The implication of these findings is the need to provide investment literacy to students so that those with talent and a willingness to take risks can make optimal investment decisions. Educational programs and policies that encourage students to invest need to be formulated and developed.